Countryside in Jan Cep's Works - Komarek, Karel (Bohemica Olomucensia, 2012)
In the prose writings by Czech writer Jan Cep (1902-1974), the countryside is a significant content component which serves the author to express the central ideas. The source for Cep's depiction of countryside is his native countryside in Middle Moravia. Cep depicts the countryside realistically, in an objective way at first sight, yet at the same time he expresses the metaphysical dimension of the world and life.